2016
DOI: 10.1177/0193945916654907
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Outcomes of a Qigong Intervention Among Community-Dwelling Aging Adults

Abstract: Aging causes various changes in body composition, which are critical implications for health and physical functioning in aging adults. The aim of this study was to explore the body composition outcomes of a qigong intervention among community-dwelling aging adults. This was a quasi-experimental study in which 90 participants were recruited. Forty-eight participants (experimental group) attended a 30-min qigong program 3 times per week for 12 weeks, whereas 42 participants (control group) continued performing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Chen et al [ 27 ], who conducted a pilot trial of Qigong therapy for 10 cases with arthritis, found improvements in pain and movement disability was decreased as was anxiety for a considerable period of post-Qigong treatment. Also noteworthy is the fact that Qigong participation can benefit body composition positively [ 16 , 28 ], which could be extremely helpful for people with arthritis, who are often excessively overweight. However, according to results of a recent randomized controlled trial that examined the effects of external Qigong therapy for people with knee osteoarthritis, if this form of Qigong is used, the benefits may vary dependent on the characteristics of the healer [ 27 ].…”
Section: Qigong As Exercise Therapymentioning
confidence: 99%
“…Chen et al [ 27 ], who conducted a pilot trial of Qigong therapy for 10 cases with arthritis, found improvements in pain and movement disability was decreased as was anxiety for a considerable period of post-Qigong treatment. Also noteworthy is the fact that Qigong participation can benefit body composition positively [ 16 , 28 ], which could be extremely helpful for people with arthritis, who are often excessively overweight. However, according to results of a recent randomized controlled trial that examined the effects of external Qigong therapy for people with knee osteoarthritis, if this form of Qigong is used, the benefits may vary dependent on the characteristics of the healer [ 27 ].…”
Section: Qigong As Exercise Therapymentioning
confidence: 99%
“…Practicing Qigong in groups is commonly undertaken to help promote team building and social support. There is a growing body of evidence for the therapeutic effects of Qigong, with regard to general health benefits, body composition, chronic disease prevention and management [31,32,33]. It is a system of gentle physical exercises and breathing control related to Tai Chi, which could be delivered in a worksite setting, at low cost, individually or with peers.…”
Section: Introductionmentioning
confidence: 99%
“…Qigong is a form of exercise that is safe and cost-effective (Horowitz, 2009). It is a suitable daily activity for older adults in nursing homes because it consists of slow gentle meditative movements that are low-impact and low-intensity, it is easy to learn, and it can be practiced at almost any location and at any time by all age groups (Chang & Chen, 2016;Kuan et al 2012;Wang et al, 2013). Qigong exercise has been found to reduce depression and to improve self-efficacy and well-being in older adults, also in those with a chronic physical illness (Tsang, Fung, Chan, Lee, & Chan, 2006;Tsang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%